ADOPSI GENERATIVE AI DI SEKOLAH DASAR: TINJAUAN LITERATUR SISTEMATIS BERBASIS KERANGKA TPACK DAN TAM - Daeli, Yaparno Famahato; Sholeh, Muh; Prasetya, Agung Tri; Avrilianda, Decky (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The emergence of Generative AI (GenAI) has the potential to disrupt primary education, yet teachers' readiness to adopt it remains fragmented. This study aims to synthesize literature regarding the adoption of GenAI by primary school teachers by developing an integrated conceptual framework based on Technological Pedagogical Content Knowledge (TPACK) and the Technology Acceptance Model (TAM). A Systematic Literature Review (SLR) was conducted following the PRISMA guidelines. Through a search across Scopus, Lens.org, and Semantic Scholar databases, an initial 194 articles were rigorously screened down to 26 final articles. The review reveals that teachers' adoption intentions are strongly driven by perceived usefulness and ease of use (TAM), particularly for instructional design efficiency. However, the quality of pedagogical integration heavily relies on teachers' TPACK proficiency to avoid passive acceptance and AI information bias. Practical implementation is hindered by digital infrastructure divides, low AI literacy, and ethical concerns regarding privacy and students' cognitive overreliance. This study proposes a conceptual framework where TPACK acts as a foundational prerequisite and TAM as a behavioral catalyst, strictly moderated by facilitating conditions and regulations. In conclusion, GenAI adoption demands a redefinition of the teacher's role from an information provider to a critical content curator and value mediator in the classroom.